Atazanavir Is a Competitive Inhibitor of SARS-CoV-2 Mpro, Impairing Variants Replication In Vitro and In Vivo - Otávio Augusto Chaves; Carolina Q. Sacramento; André C. Ferreira; Mayara Mattos; Natalia Fintelman-Rodrigues; Jairo R. Temerozo; Leonardo Vazquez; Douglas Pereira Pinto; Gabriel P. E. da Silveira; Laís Bastos da Fonseca; Heliana Martins Pereira; Aluana Santana Carlos; et al. (MDPI AG, 2021)
Atazanavir (ATV) has already been considered as a potential repurposing drug to 2019 coronavirus disease (COVID-19); however, there are controversial reports on its mechanism of action and effectiveness as anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Through the pre-clinical chain of experiments: enzymatic, molecular docking, cell-based and in vivo assays, it is demonstrated here that both SARS-CoV-2 B.1 lineage and variant of concern gamma are susceptible to this antiretroviral. Enzymatic assays and molecular docking calculations showed that SARS-CoV-2 main protease (Mpro) was inhibited by ATV, with Morrison's inhibitory constant (Ki) 1.5-fold higher than GC376 (a positive control) dependent of the catalytic water (H2Ocat) content. ATV was a competitive inhibitor, increasing the Mpro's Michaelis-Menten (Km) more than sixfold. Cell-based assays indicated that different lineages of SARS-CoV-2 is susceptible to ATV. Using oral administration of ATV in mice to reach plasmatic exposure similar to humans, transgenic mice expression in human angiotensin converting enzyme 2 (K18-hACE2) were partially protected against lethal challenge with SARS-CoV-2 gamma. Moreover, less cell death and inflammation were observed in the lung from infected and treated mice. Our studies may contribute to a better comprehension of the Mpro/ATV interaction, which could pave the way to the development of specific inhibitors of this viral protease.